STUDI KASUS: Feline Infectious Peritonitis (FIP) TIPE EFUSIF PADA KUCING TINA - Hamin, Armando Wandiri (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2023)
Feline infectious peritonitis (FIP) is a viral infection with a high mortality rate in cats. This disease is caused by a coronavirus (FCoV). FIP has two types namely wet type (effusive) and dry type (non effusive). Clinical symptoms in this case include anorexia, lethargy, jaundice, fever, and significant weight loss. The wet type causes about 70-80% of all cases of this disease and is more malignant than the dry type. The wet type is characterized by an accumulation of fluid in the abdominal cavity, chest cavity, or both. FIP case in the cat Tina, weight 2.99 kg, body temperature 40.30°C, normal CRT, female sex, 11 months old with calico hair color. Supporting diagnoses are generally needed to confirm the diagnosis of FIP because this disease does not have specific symptoms. Some supporting diagnostic tools for Bela cats are rapid FIP antibody tests. The differential diagnosis of this case was ascites due to FIP compared to ascites due to congestive heart failure or hypoproteinemia (kidney and liver disease), pregnancy, and trauma. Treatment in this case is furosemide, tolfedin, ornipural, channa blister, cefotaxime, samilyn and Exterminate FIP.